Acute Coronary Syndrome Screening and Diagnostic Practice Variation. (8th May 2017) - Yiadom, Maame Yaa A. B.; Liu, Xulei; McWade, Conor M.; Liu, Dandan; Storrow, Alan B.
Abstract: Background: In the absence of the existing acute coronary syndrome (ACS) guidelines directing the clinical practice implementation of emergency department (ED) screening and diagnosis, there is variable screening and diagnostic clinical practice across ED facilities. This practice diversity may be warranted. Understanding the variability may identify opportunities for more consistent practice. Methods: This is a cross‐sectional clinical practice epidemiology study with the ED as the unit of analysis characterizing variability in the ACS evaluation across 62 diverse EDs. We explored three domains of screening and diagnostic practice: 1) variability in criteria used by EDs to identify patients for an early electrocardiogram (ECG) to diagnose ST‐elevation myocardial infarction (STEMI), 2) nonuniform troponin biomarker and formalized pre‐troponin risk stratification use for the diagnosis of non‐ST‐elevation myocardial infarction (NSTEMI), and 3) variation in the use of noninvasive testing (NIVT) to identify obstructive coronary artery disease or detect inducible ischemia. Results: We found that 85% of EDs utilize a formal triage protocol to screen patients for an early ECG to diagnose STEMI. Of these, 17% use chest pain as the sole criteria. For the diagnosis of NSTEMI, 58% use intervals ≥4 hours for a second troponin and 34% routinely risk stratify before troponin testing. For the diagnosis of noninfarction ischemia, the median percentage of patients who have NIVT performed during their ED visit is 5%. The median percentage of patients referred for NIVT in hospital (observation or admission) is 61%. Coronary CT angiography is used in 66% of EDs. Exercise treadmill testing is the most frequently reported first‐line NIVT (42%). Conclusion: Our results suggest highly variable ACS screening and clinical practice.